Implementation of a Sero Survey For Sars-Cov-2 at The Medan City Health Office in 2023 - Ismah, Zata; Yustika, Dilla; Siregar, Ridha Panalia; Harahap, Sunnii Irtiyah (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
A sero survey was conducted to see the total population in Indonesia who already have antibodies against the SARS-CoV-2 virus. The sero survey method uses a blood test to check the body's antibodies to the virus. The type of research used is qualitative research with in-depth interview techniques and also field observations. The sero survey conducted in the Medan City Region was in 10 Sub-Districts and 4 Community Health Centers with a sample target for the entire Medan City area of 205 samples. The results showed that the implementation of the serosurvey at the Medan City Health Office was going well, but the target respondents had not reached 100%.